The importance of mutual consent in social relationships under the shariah - Wan Muhammad, Ramizah; Jahn Kassim, Puteri Nemie (American Institute for Policy Development, 2016)
Consent is recognized under Islamic Law as a necessary element in any social relationship (mu`amalat) between individuals. The importance of mutual consent between parties is regarded as predominant in various economic and non-economic activities, including business transactions, marriage contracts, punishment of criminal offenders and even for those seeking medical treatment. Thus, the requirement for mutual consent is indispensable in any transaction, without which the contract will be declared as null and void and ultimately, carries no legal effect. This is based on Qur'anic verse which states: “O you who have believed, do not consume one another's wealth unjustly but only [in lawful] business by mutual consent” (4:29). The Prophet Muhammad has also been reported to have said: “Sale is but based on mutual consent”. These evidences clearly depict that all transactions must be based on free willingness of parties involved and the principles governing consent under the Shariáh have three basic elements, which are, (i) Intention (Niyyah); (ii) Will (Irādah); and (iii) Choice (Ikhtiyār). Consent is regarded as an indispensable element which must be obtained prior to any procedure of medical treatment. A doctor is under a duty to obtain consent from his patient beginning from the stage of informing the material risks to the patient until the completion of the medical treatment. Once consent has been obtained in accordance with the demands of the Shariáh, then only the medical treatment will be considered to have been legally performed.